The quality of health research for young Indigenous Australians: systematic review. Issue 1 (8th July 2013) - Azzopardi, Peter S; Kennedy, Elissa C; Patton, George C; Power, Robert; Roseby, Robert D; Sawyer, Susan M; Brown, Alex D
Abstract: Objective: To assess the extent and quality of the evidence base related to the health and wellbeing of young Indigenous Australians. Study design: Systematic review of peer‐reviewed literature; grading of quality of literature; mapping of sample characteristics and study foci. Data sources: English language publications, 1 Jan 1994 – 1 Jan 2011 in MEDLINE, ERIC, CINAHL, EMBASE, ATSIhealth, PsycINFO, the Cochrane Library and the Australian Indigenous HealthInfoNet. Study selection: Inclusion criteria were: published 1 Jan 1994 – 1 Jan 2011; original peer‐reviewed research; reported data for Australian Aboriginal and Torres Strait Islanders aged 10–24 years; focused on health and wellbeing. Grading for quality included ascertainment of Indigenous status, representativeness of the sample for the target population, and quality of measures of exposure and outcome. Data synthesis: 360 peer‐reviewed publications met inclusion criteria; 90 (25%) exclusively sampled Indigenous young people. 250 studies (69%) were of good‐quality design; 124 of these focused on health outcomes (15 of these evaluated an intervention) and 116 focused on health‐risk exposure (26 evaluative). The methodological quality of data improved during 1994–2010; however, only 17% of studies focused on urban populations. A third of good‐quality studies of health outcome focused on communicable diseases such as sexually transmitted infections and tuberculosis. There was good‐quality data for oral health and substance use, and some data for adolescent pregnancy. Data on mental disorders, injury and cause‐specific mortality were limited. Conclusions: Despite improvements, there are important gaps in the evidence base for the health of young Indigenous Australians. Our study points to the need for greater research investment in urban settings and with regard to mental disorders and injury, with a further emphasis on trials of preventive and clinical intervention.